Development of tobacco inter-MITE polymorphism (IMP) markers and its application in genetic mapping - GAO Yu-long; GUI Yi-jie; XIAO Bing-guang; BO Shi-ping; YAN Guang-hao; FAN Long-jiang (浙江大学学报. 农业与生命科学版)
DNA transposable elements require the transposase from an autonomous parent element for transposition. The characteristic of MITEs are generally less than 500 bp with terminal inverted repeat (TIR) and target site duplication (TSD). MITEs often insert into insides of genes or regions near to genes, and therefore the markers based on TIRs of MITEs, termed inter-MITE polymorphism (IMP), are possibly lined to important agricultural traits and have been successfully used in barley, wheat, maize, oats etc. Extremely low polymorphism has been observed in tobacco by several molecular marker systems, such as RAPD, AFLP, ISSR, SRAP and SSR, due to its narrow genetic background during domestication. In this study, IMP markers were developed in tobacco using genomic sequences from the Tobacco Genome Initiative (TGI).Non-redundant tobacco genomic sequences from TGI were used to scan MITEs through a bioinformatic approach and 11 581 MITEs of unique TIRs were eventually identified and aligned (partial result was shown in Fig. 2). Two hundred and nineteen IMP primers were designed according to the alignments and then were tested among nine representative tobacco varieties with different types (flue-cured, burley, oriental and cigar tobacco) (Table 1). In the 219 primers, 119 were successfully amplified by PCR, which demonstrated a success rate of 54.6% (partial result was shown in Fig. 3). The 119 primers were further used in a doubled haploid (DH) population of a flue-cured tobacco, 29 of which showed polymorphism between the two parental lines (Honghuadajinyuan/Hicks Broadleaf). Of the 29, 21 were genotyped in the DH population and integrated into seven linkage groups with SSR markers (Fig. 5).Our results demonstrate that IMP markers are useful in tobacco such as genetic germplasm investigation and genetic map construction. But low development efficiency is also observed for this kind of marker system in tobacco. To improve the efficiency of IMP marker development, high-throughput detective/scanning platforms are needed in its genotyping process.